High Prevalence of HIV-Related Cryptococcosis and Increased Resistance to Fluconazole of the Cryptococcus neoformans Complex in Jiangxi Province, South Central China - Yang, Chunxi; Bian, Zeyuan; Blechert, Oliver; Deng, Fengyi; Chen, Hui; Li, Yueting; Yang, Yunhong; Chen, Min; Zhan, Ping (Frontiers in Cellular and Infection Microbiology, 2021)
Cryptococcosis is caused by fungi of the Cryptococcus neoformans/Cryptococcus gattii complex and is a severe concern for public health worldwide. C. neoformans species are globally distributed, and C. gattii species are mostly found in America, Australia and Sub-Saharan Africa. Cryptococcus usually infects an immunocompromised population; however, the majority of cryptococcosis in China has been reported in patients without any recognizable immunosuppression, i.e., HIV infection. Very few studies investigated this disease in South Central China. This study recruited 230 clinically suspected cryptococcosis cases in the last 5 years at two hospitals in Jiangxi Province. All isolated strains were subjected to multilocus sequence typing (MLST) and phylogenetic analysis. Serotype and mating type were assessed by PCR, in vitro antifungal susceptibility was assessed by the CLSI-M27-A3 protocol. A total of 230 patients were identified as infected by C. neoformans, including 12 cases with Talaromyces marneffei coinfection. All seven MLST markers were successfully amplified and used to identify the ST genotype in 199 strains. C. gattii strains were not detected. In contrast to previous studies, 59.3% of the patients had an immunocompromised status, and 61.9% of these patients were infected with HIV. All isolates manifested serotype A and mating type α. The ST5 genotype was common (89.5%) in the Jiangxi region, and three novel genotypes (ST656, ST657, and ST658 in six isolates) were detected in the present study. Eighty-six of the isolates (43.2%) were not sensitive to fluconazole at a MIC50 ≥8 μg/ml, most of isolates were resistant to amphotericin B, and nearly all isolates were resistant to itraconazole and posaconazole. Resistances to 5-Flucytosine and voriconazole were very rare. The results of the present study indicated that C. neoformans is the predominant species for cryptococcosis in Jiangxi Province, and a large proportion of strains were not sensitive to FLU, which may be related to treatment failure and relapse. A high percentage of HIV-related C. neoformans infections was reported in Jiangxi, supporting previous hypothesis that cryptococcosis is more frequent among HIV-infected population in China. Continuous monitoring of species distribution and antifungal sensitivity is important for investigation of this severe disease in the Jiangxi region.